Case for diagnosis. Ulcer and papular lesions in a patient with diabetes mellitus. Protothecosis, - Larissa Daniele Machado Góes; Vinícius da Silva Monteiro; Ana Tereza Orsi de Souza (Sociedade Brasileira de Dermatologia, 2021)
Abstract Protothecosis is a rare disease caused by achlorophilic algae of the genus Prototheca spp. In general, three clinical forms are observed: cutaneous, articular and systemic. The cutaneous form is the most common one. This study describes a patient with isolated erythematous papules and erythematous papular plaques in the scapular regions, with a previous histopathological diagnosis of cryptococcosis. New tests were conclusive for the diagnosis of protothecosis, caused by Prototheca wickerhamii.